Development of decision support systems manager credit bank - Зосімович, М.В.; Молодецька, К.В. (Proceedings of National Aviation University, 2008)
There was designed the software for innovation projects evaluation. The application of a decision assumption support by a bank manager of Credit Department allows to improve the quality of managing process, timeliness of making the right decision in problem situations, which are characterized by high complexity, uncertainly and weak structuralism.